Pengembangan Modul Ajar Berbasis Masalah Dengan Pendekatan Realistics Mathematic Educations Untuk Meningkatkan Kemampuan Pemecahan Masalah Geometri Siswa SD - Siti Aisyah; Sukmawarti Sukmawarti (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The objective of this study is to determine the feasibility of a geometry teaching module design based on Realistic Mathematics Education (RME) to improve students' learning outcomes. It also aims to identify the improvement in elementary school students' geometry problem-solving skills through the implementation of the RME-based geometry teaching module. This research is a type of development research (Research and Development) using the 4D development model proposed by Thiagarajan. In this study, the researcher implemented the 4D development procedure only up to the third stage, namely development, since the focus of this study is solely on developing a problem-based module using the RME approach. The instruments used for data collection were questionnaires administered to expert validators, including subject matter experts and learning design experts. Based on the research results, the RME-based geometry teaching module design is considered highly feasible for improving the learning outcomes of fifth-grade students at SD Negeri 101797 Deli Tua. The geometry problem-solving skills of elementary school students showed a significant improvement through the implementation of the RME-based teaching module. The pre-test results before using the module showed an average student problem-solving score of 30.4. After using the teaching module design, the average score increased to 85.3. Therefore, the RME-based teaching module is highly recommended for enhancing students' problem-solving abilities in the topic of two-dimensional geometry.